Pseudo-dynamic tests of a full-scale CFT Specimen design, experiment and analysis. - Tsai, Keh-Chyuan
A series of pseudo-dynamic tests (PDTs) of a full-scale 3-story 3-bay buckling-restrained braced frame (BRBF) using concrete-filled tube columns was tested in the Taiwan National Center for Research on Earthquake Engineering using networked PDT techniques in October 2003. During the tests, real-time experimental responses and video were webcasted to Internet viewers. The input ground motions adopted for the PDTs were chosen from the 1999 Chi-Chi and the 1989 Loma Prieta earthquakes and scaled to represent three seismic hazard levels. This paper is in two parts, focusing on the investigations of the overall structure and the local members. This paper constitutes Part I and discusses the design, analytical investigations, and key experimental results of the specimen frame, such as the buckling of the brace-to-gusset joints. Part II of the paper, the companion paper, describes the gusset stiffening schemes and detailed experimental behavior of the BRBs and their connections. Experimental peak inter-story drifts of 0.019 and 0.023 radians, prescribed for the design basis and the maximum credible earthquakes, respectively, are within the target design limits of 0.020 and 0.025 radians. These tests confirmed that the PISA3D and OpenSees nonlinear structural analysis computer programs can simulate the experimental peak shears and floor displacements well.
Keywords: Concrete-filled tube (CFT).; Buckling-restrained brace; Displacement-based seismic design; Networked pseudo-dynamic test; Nonlinear structural analysis